Cost-Based Evaluation of INA – CBG's Rates in Patients with Type II Diabetes Mellitus Inpatient at Royal Prima Public Hospital Medan - Febri Sri Astuti Marpaung; Ermi Girsang; Yolanda Eliza Putri Lubis (CV. Inara, 2023)
RSU Royal Prima Medan applies the Indonesian Case Based Groups (INA-CBGs) system as a payment system for health services for JKN-BPJS patients. This study describes the implementation of the INA-CBGs system in inpatients with Type 2 Diabetes Mellitus. This research is descriptive research with a qualitative approach. The population of this study are people who play a role in calculating BPJS financing at RSU Royal Prima Medan. The sample used in this study amounted to 4 informants consisting of 1 informant in the BPJS patient register section, 1 Head informant in the BPJS financing calculation section, and 2 staff informants in the BPJS financing calculation section. Data analysis using the Triagulation method. The results showed that the majority of Type II DM patients at RSU Royal Prima Medan were > 50 years old, as many as 29 patients with a percentage of 85.3%, and 15 patients for male and 19 female patients. The implementation of the INA – CBG's system at RSU Royal Prima Medan for inpatients with Type II DM is in accordance with the procedure, the obstacles faced by officers such as when entering data where there are still many writings from doctors that are difficult to understand, the tariff for INA – CBG's packages for Type II DM patients Hospitalization at RSU Royal Prima Medan is adjusted to the patient's condition and to assess the success of implementing the INA – CBG's system at RSU Royal Prima Medan for inpatients with Type II DM as seen from the hospital's income where during the implementation of the INA-CBGs system the hospital did not experience losses, even hospital revenue exceeds the target to be achieved.